Additive manufacturing in radiation oncology: a review of clinical practice, emerging trends and research opportunities. (17th February 2020) - Tino, Rance; Leary, Martin; Yeo, Adam; Kyriakou, Elizabeth; Kron, Tomas; Brandt, Milan
Abstract: The additive manufacturing (AM) process plays an important role in enabling cross-disciplinary research in engineering and personalised medicine. Commercially available clinical tools currently utilised in radiotherapy are typically based on traditional manufacturing processes, often leading to non-conformal geometries, time-consuming manufacturing process and high costs. An emerging application explores the design and development of patient-specific clinical tools using AM to optimise treatment outcomes among cancer patients receiving radiation therapy. In this review, we: highlight the key advantages of AM in radiotherapy where rapid prototyping allows for patient-specific manufacture explore common clinical workflows involving radiotherapy tools such as bolus, compensators, anthropomorphic phantoms, immobilisers, and brachytherapy moulds; and investigate how current AM processes are exploited by researchers to achieve patient tissue-like imaging and dose attenuations. Finally, significant AM research opportunities in this space are highlighted for their future advancements in radiotherapy for diagnostic and clinical research applications.